The Effect of Combined Cinnamon and Ginger Decoction on Fasting Blood Glucose Levels among Patients with Diabetes Mellitus in RT 02 RW 04 Kampung Sukamanah, Parung Panjang, Bogor - Luthfia Rahmi; Achirman Achirman; Gaung Eka Ramadhan (Jurnal Kesehatan dan Kedokteran, 2026)
Diabetes mellitus is a chronic metabolic disease that requires continuous management to prevent complications and improve patients’ quality of life. In community settings, several patients still experience uncontrolled blood glucose levels due to limited awareness, lifestyle factors, and inconsistent treatment adherence. Cinnamon and ginger are herbal ingredients that contain bioactive compounds and are commonly used as complementary approaches to support blood glucose management. Objective: This study aimed to examine the effect of a combination of cinnamon and ginger decoction on reducing fasting blood glucose levels among patients with diabetes mellitus in RT 02 RW 04 Kampung Sukamanah, Parung Panjang, Bogor. Methods: This study used a quantitative quasi-experimental design with a pretest–posttest without control group approach. A total of 18 respondents with diabetes mellitus were selected using purposive sampling based on predetermined inclusion criteria. Fasting blood glucose levels were measured before and after the administration of cinnamon and ginger decoction. Data were analyzed using univariate analysis and a paired sample t-test to determine differences in blood glucose levels before and after the intervention. Findings: The results showed that the mean fasting blood glucose level before the intervention was 373.72 mg/dL, while the mean level after the intervention decreased to 182.89 mg/dL. Statistical analysis showed a significant difference between pre-test and post-test blood glucose levels, with a p-value of 0.001. These findings indicate that the administration of cinnamon and ginger decoction was associated with a reduction in fasting blood glucose levels among the respondents. Implication: The findings suggest that cinnamon and ginger decoction may be considered as an affordable and accessible complementary non-pharmacological approach to support community-based diabetes management. However, this intervention should not replace standard medical treatment. Originality: This study provides empirical evidence on the combined use of cinnamon and ginger decoction in a community-based setting, particularly among patients with diabetes mellitus in RT 02 RW 04 Kampung Sukamanah, Parung Panjang, Bogor.